Before I go - Oakley, Colleen (Gallery Books, 2015)
On the eve of what was supposed to be a triumphant "Cancerversary" with her husband Jack to celebrate three years of being cancer-free, Daisy suffers a devastating blow: her doctor tells her that the cancer is back, but this time it's an aggressive stage four diagnosis. She may have as few as four months left to live. She's terrified of what will happen to her brilliant but helpless husband when she's no longer there to take care of him. The solution: she has to find him another wife.